Deteksi Dini Stunting Pada Balita Di Klinik Mariana Desa Tanjung Rejo - Eva Hotmaria Simanjuttak; Friska Margareth Parapat; Netti Meilani Simanjuttak (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
The golden period of humans starts from the fetus in the womb until the age of 2 years, this period is very important in the growth and development of children. Children who are stunted as a result of inadequate intake or repeated infections are at greater risk for stunting. The purpose of this community service is to check the condition of toddlers whether they are stunted or not. Provide education or counseling related to toddler growth and involve parents. Increase the knowledge of mothers who have toddlers about stunting. This activity is carried out by conducting anthropometric examinations to toddlers and providing education to parents about the results of the examinations carried out. Based on the results of stunting detection, 32 children (91.43%) were not stunted and 3 children were stunted (8.57%). This stunting early detection activity is a forum for monitoring and obtaining information about the anthropometric development of toddlers so that they are able to prevent stunting.